Golden lettering, Rajesh Mansion - Ghosh, Ayan (Jio Institute, 2023)
Broadway font made from metal in gold polish, lettering used at Rajesh Mansion. The mansion was formerly known as Sorab Mansion and designed by architect G. B. Mhatre in collaboration with Contractor Kanga & Co.